Implementasi pembiasaan literasi dan jum'at bersih untuk meningkatkan civic skills peserta didik - padilah, siti nur padilah; Rahmatiani, Lusiana; Saylendra, Nadya Putri (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2024)
At this time, the flow of globalization is an extraordinary development to provide aspects of human life, especially education, skills that must be possessed by students. The aim of this research is to determine the implementation of positive literacy habits and clean Fridays to improve students' civic skills at SMAN 5 Karawang. This study used descriptive qualitative method. Data collection techniques through observation, interviews and documentation. This is because the teacher provides several good strategies during language literacy activities and clean Fridays so that students have intellectual skills and participation skills, forming students into the nation's next generation who are intelligent and full of responsibility, able to use language. good foreigner, able to build cooperation, able to carry out and complete tasks as well as possible, actively participate in various existing activities in a good way and take responsibility for future provisions